Implementation of New Technologies in the Water Supply and Wastewater Discharge System (Texas Journal of Engineering and Technology, 2024)
In the article, the water supply system, water intake facilities within the complex of its facilities, water preparation and delivery to consumers are considered important. The efficiency of the system is ensured by increasing the efficiency of water intake facilities, and this requires modern technologies. Sewage networks are used independently. Therefore, the pipes are laid with a certain slope. In order to be convenient from the economic point of view, the preferred form of sewage networks should be chosen.